A Rapid, Accurate, Single Molecule Counting Method Detects Clostridium difficile Toxin B in Stool Samples - Gite, Sadanand (Sci Rep, 2018)
We describe a new rapid and accurate immunoassay-based technology capable of counting single target molecules using digital imaging without magnification. Using the technology, we developed a rapid test for Clostridium difficile toxin B, which is responsible for the pathology underlying potentially fatal C. difficile infections (CDI). There are currently no tests for CDI that are rapid, sensitive, and specific. The MultiPath C. difficile toxin B test images and counts complexes of target-specific magnetic and fluorescent particles that have been tethered together by toxin B molecules in minimally processed stool samples. The performance characteristics of the 30 minute test include a limit of detection of 45 pg/mL, dynamic range covering 4–5 orders of magnitude, and coefficient of variation of less than 10%. The MultiPath test detected all toxinotypes and ribotypes tested, including the one most commonly occurring in the US and EU; shows no cross reactivity with relevant bacterial species; and is robust to potential interferants commonly present in stool samples. On a training set of 320 clinical stool samples, the MultiPath C. difficile toxin B test showed 97.0% sensitivity (95% CI, 91.4–99.4%); 98.3% specificity (95% CI, 96.8–99.2%); and 98.2% accuracy (95% CI, 96.7–99.0%) compared to the cellular cytotoxicity neutralization assay (CCNA) reference method. Based on these compelling performance characteristics, we believe the MultiPath technology can address the lack of rapid, sensitive, specific, and easy-to-use diagnostic tests for C. difficile.